Political Financing and It’s Impact on The Quality of Democracy in Southeast Asia - Deasy Simandjuntak (Association for Elections and Democracy (Perludem), 2021)
Across the region, it is generally assumed that funding for parties and campaigns derives from sources such as membership fees, voluntary work by members and/or financial contributions by wealthy individual and interest groups. Yet what are the similarities and differences among the regimes and practices of political financing the region, and how do we understand the quality of democracy by looking at their political financing? Malaysia, Indonesia, Thailand and Myanmar have had their elections in the past three years. The article gives an overview of the countries’ political financing regimes and/or practices to identify common denominators as well as draw linkage between political financing sources and democratic quality.